Valuation of privatization in Europe by experts and stakeholders: results of explorative surveys and interviews. EU-supported project understanding privatization policy: political economy and welfare effects - Gernot Nerb; Siegfried Schönherr; Bennet Schroeder (ifo Institut für Wirtschaftsforschung an der Universität München, 2008)
This EU supported Specific Targeted Research Project (STREP) had been conducted by a European Consortium composed of eight research institutions. Ifo's part within this larger programme was (a) to analyse the fiscal effects of privatization and (b) to assess the valuation of privatization effects by stakeholders and experts in nine European countries. For the fiscal effects a model was constructed based on comparing investment decisions of firms with public investment decisions and tested with data from US municipalities. Than the model was used to analyse privatization effects in comparison with public investment effects. The results showed close similarities between public investment and privatization effects. The model then was applied to German conditions. The results of both tests are published (in preparation) in three articles. The valuation of privatization effects was explored by two standardized surveys and about 50 face to face interviews in nine European countries. The results have been published in IFO Studien No 43.
Keywords: L30; 330; Privatisierung; Wirtschaftspolitische Wirkungsanalyse; Meinung; Sachverständiger; Führungskräfte; EU-Staaten; Privatisierung; Wirkungsanalyse; Meinung; Experten; Führungskräfte; EU-Staaten; Frankreich; Spanien; Polen; Großbritannien; Deutschland; Österreich; Italien; Griechenland; Ungarn